Radość życia. O kreatywnym sposobie istnienia czło− wieka - ŻYWCZOK, Alicja (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
The current article presents an attempt to grasp the essential similarities and differences between the scopes of the concepts of happiness, joy and pleasure, which are very important in Karol Wojtyła’s moral philosophy. The author stresses that the capability of joie de vivre is a mental disposition which is ontologically significant not only due to the fact that it is inherently bound up with the human being, but also because it performs therapeutic functions. The author then presents an insight into the ontogenetic evolution of joie de vivre, analyzing its simplest, biological forms, as well as the spiritual and metaphysical modes of the affirmation of life. The author also puts forward the thesis that the education towards joy is enhanced by the teacher’s understanding of numerous sources from which human joy springs, such as encounter with the Transcendence, unity with others, the didactic environment of love, truth and freedom, as well as by the conviction that it is an essential task to lead the pupils out of the existential states that undermine joie de vivre. The final part of the article includes some praxeological clues helpful in education of the youth towards joie de vivre. Translated by Dorota Chabrajska